3D Modeling of Geothermal Reservoirs: Case Study from Subtatric Basin in Western Carpathians, Slovakia - Hlavacova, Lucia (2009)
RES Master´s Thesis Verkefnið er unnið í tengslum við Háskóla Íslands og Háskólann á Akureyri Geothermal energy is a potential renewable energy source that should be taken into account by the Slovak government. To aid geothermal exploration, 3D modeling is a very useful tool. The objective of this project was to model Poprad basin and the northern part of Hornad basin, in the Inner Carpathian system in Slovakia, to assess future prospective geothermal areas. These two are considered active geothermal areas. The main aquifers are built by Triassic carbonates – dolomites and limestones of Choc and Krizna nappe. In the central part of the Poprad basin, on the basis of seismic interpretation, Choc nappe thicknesses from 200 to 1100 m were obtained. Larger nappe thicknesses from 1200 to 1500 m were obtained on the east and southeast part of the studied area. The average value of the temperature gradient reaches 32.6 – 34.5° C/km and the average value of the heat flow density was estimated on 67mW/m2. Temperatures on the top of the Pre-Paleogene basement reach 50 – 85° C. In this work the geologic structure of the Gerlachov area, which is situated in the northwestern part of Poprad Basin, was also interpreted. From a geothermal point of view the formations with the most potential are Mesozoic units represented by Choc and Krizna Nappes underlying Paleogene rocks. Based on the geologic composition of Choc Nappe, the existence of very good conditions for a geothermal water reservoir can be expected. Krizna Nappe has less positive conditions for geothermal waters exploitation. General discharge of groundwater in Choc Nappe should be more than 22 l.s-1. The temperature in Choc Nappe is between 35 and 45° C.